1988
DOI: 10.1038/bjc.1988.185
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and menstrual cycle upon proliferative activity of the normal human breast

Abstract: 3Pathology and 4Surgery, Christie and Withington Hospitals, Manchester M20 9BX, UK.Summary The aim of this study was to determine the proliferative activity within the epithelial cells of the normal human breast in 122 patients (6 reduction mammoplasties and 116 fibroadenoma excisions) in relation to age and the phase of the menstrual cycle. Thirty three of the patients were on oral contraceptives and 33 were parous.Thin tissue slices were incubated with tritiated thymidine and processed for autoradiography. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
112
2
7

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(132 citation statements)
references
References 26 publications
(36 reference statements)
11
112
2
7
Order By: Relevance
“…This also allow s comparison with many of the studies of premenopausal breast. which considered lobular epithelium only (Anderson et al 1982: Potten et al 1988: Williams et al 1991 Figure 1A) and found to be unrelated to patient age (within the range of 49-68 years) (n = Il1. rho = 0.002.…”
Section: Ki67 Labellingmentioning
confidence: 95%
See 2 more Smart Citations
“…This also allow s comparison with many of the studies of premenopausal breast. which considered lobular epithelium only (Anderson et al 1982: Potten et al 1988: Williams et al 1991 Figure 1A) and found to be unrelated to patient age (within the range of 49-68 years) (n = Il1. rho = 0.002.…”
Section: Ki67 Labellingmentioning
confidence: 95%
“…-stimulation and the lowered proliferation rates that we have demonstrated. It is well documented that age also exerts a significant negative effect upon proliferation in premenopausal (Meyer 1977: Anderson et al 1982: Potten et al 1988) and postmenopausal (Mever and Connor. 1982) breast epithelium.…”
Section: Ki67 Labellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of sex steroid hormones and hormonally mediated factors on human breast tissue proliferative rates has been reported by Anderson et al 89 and Potten et al 90 Anderson et al used 3H-thymidine labeling and autoradiography on biopsy material from benign breast lesions. They observed higher labeling indexes from (1) younger versus older women (or women with recent versus remote menarche), (2) luteal versus follicular phase of the menstrual cycle, (3) users of oral contraceptives versus nonusers (primarily in nulliparous women), and (4) high estrogen dosage versus low dose oral contraceptive^.^^ Potten et al used similar methods and materials and obtained similar findings with respect to patient age and menstrual cycle phase.'"…”
Section: Cell Proliferationmentioning
confidence: 99%
“…The lobules will develop more during the luteal phase, the second half of the cycle after ovulation, and more mitotic activity is seen. If no pregnancy occurs, these changes degenerate [3].…”
Section: Breast Developmentmentioning
confidence: 99%